Romantic bias in judging the attractiveness of faces wearing masks - Machi Sugai (i-Perception, 2024)
The spread of COVID-19 has drastically increased the number of people wearing masks in public areas and the opportunities to evaluate others’ faces based on limited information. This study investigates the cognitive bias in judging the attractiveness of faces partially hidden by sanitary masks. Experiment 1 revealed that men rated women's faces as more attractive when wearing masks, specifically in the context of rating women as romantic partners; however, this mask bias was absent when men rated women as friends. On the other hand, women did not show the mask bias irrespective of the assumed social relationship. Experiment 2 demonstrated that the mask bias among elderly men was less affected by the assumed social relationship (or the possibility of reproduction), compared to young men, though they showed the bias itself. These results suggest that the cognitive strategies related to reproduction underlie the attractiveness judgment of the partial faces.